SISTEM PENGOLAHAN LIMBAH CAIR INDUSTRI PRODUK PERIKANAN - Achmad Muflih (Faculty of Science and Technology University Ibrahimy, 2013)
Fishery product processing industry consumes water reaches 20 m3 / ton of product produced depending on the technology used, the type of fish that is processed and the resulting product. The resulting liquid waste containing organic matter with loads up to 20 kg BOD / ton. The highest burden of waste which comes from the canning industry and the manufacture of fishmeal (fishmeal). New sewage processed aims to eliminate organic load, has not reached the preliminary total nitrogen contained therein. The content of nitrite and nitrate are still high will lower the quality of receiving water bodies. Fishery wastewater treatment technology with a combination of aerobic and anoxic processes be a good option developed for the allowance of nitrogen contained in the waste